Effect of operating conditions on divinylbenzene production in diethyl benzene dehydrogenation reactor - M. E. Zeynali; H. Abedini; H. R. Sadri (Iranian Journal of Chemical Engineering)
DEB dehydrogenation reaction was conducted to produce divinylbenzene (DVB) and ethylvinylbenzene (EVB). The effects of temperature, catalyst weight and time factor on the performance of the dehydrogenation reactor were investigated experimentally. Temperature was varied from 550º C up to 600 º C. Temperature affect the conversion of DEB to DVB significantly. The mole fraction of DEB in the outlet of the reactor is reducing up to 580 º C, but further increase in temperature up to 600 º C does not decrease the mole fraction of DEB in the outlet of the reactor. Catalyst weight was varied from 10 gr up to 40 gr. The results showed that the trends of EVB+DVB production and DEB consumption are identical at various catalyst weights. To obtain optimum time factor for the DEB dehydrogenation process experiments were conducted at various time factors. The results showed that the optimum time factor for DVB as a desired product is 825 gr/hr.mole. . The data and information provided in this research can be used for scale-up and optimization purposes.